East and West: The Reconstruction of Linguists Network in the Arabic World - Abdullah, Abdullah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
This study focused on linguistic ideas aimed at building linguist networks in the East and West. It made uses of an intellectual historical method. Documents, as books and scientific publications, were used both primary and secondary data. Linguists' writings were regarded as the major source. Historical papers, journals, and books that examine linguistic ideas, commentary on them, and other literatures linked to the subject were considered secondary sources. Re-reading was used to analyze the data received, particularly the aspects that had the most serious issues, were the most apparent, and attracted the most attention from linguists' ideas. This was done in order to come up with complete and critical findings that incorporate facts, hypotheses, and viewpoints. The study found that linguists who were connected in the network of linguistic study centers played an important role in disseminating linguistic ideas, both through the teaching and works of the kitab. This study concluded that Arabic linguistics had grown and developed in Islamic discipline in order to reach the totality of understanding of Lughat al-TanzÄ«l (al-Qur'Än). In general, the phenomena that stood out in the intellectual network were (a) the phenomenon of continuity and exploration with nuances of strict simÄÊ» and qiyÄs, (b) continuity and change with nuances of simÄÊ» and loose qiyÄs, (c) new synthesis through ikhtiyÄr (selection) and intikhÄb (choice) processes with philosophical nuances, and (d) critical neo-synthesis with zhÄhiriy nuances, which simplify Ê»Ämil, taÊ»lÄ«l, and qiyÄs, ultimately affiliated to the Basrah and Kufa Network.